2020
DOI: 10.1007/s13300-020-00793-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Freestyle Libre Flash Glucose Monitoring System on Diabetes Distress Among Individuals with Type 1 Diabetes: A Prospective Study

Abstract: Aim: To study and explore the intervention of the flash glucose monitoring system (FGMS) on diabetes-related distress (DRD) in children and adolescents with type 1 diabetes (T1D). Methods: A 12-week prospective study was performed from March 2019 to July 2019 involving 187 children and adolescents (age range 13-19 years; 56.7% female) with T1D who were self-testing their glucose levels using the conventional fingerprick method. At the time of the baseline visit, FGMS sensors were fixed by a trained diabetes ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 28 publications
(40 reference statements)
1
69
0
1
Order By: Relevance
“…Such studies have focused on adult T1DM patients and European populations. A prospective study in Saudi Arabia demonstrated ; p = 0.001) [32]. A recent study reported that continuous glucose monitoring in adolescents with T1DM is associated with lower diabetes-related distress [33].…”
Section: Discussionmentioning
confidence: 96%
“…Such studies have focused on adult T1DM patients and European populations. A prospective study in Saudi Arabia demonstrated ; p = 0.001) [32]. A recent study reported that continuous glucose monitoring in adolescents with T1DM is associated with lower diabetes-related distress [33].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, that these patients maintained good glycaemic control is reassuring in terms of their effective self-management of diabetes. We speculate that the use of FGM combined with insulin pump therapy contributed to this effect [30]; for example by limiting diabetes-related distress [31].…”
Section: Discussionmentioning
confidence: 98%
“…44 Differences between capillary glucose values and sensor readings should be explained to school personnel to avoid wrong treatment decisions due to poor knowledge of the device, complemented with frequent updates when new information is available. 45 This single-center unselected pediatric population was wellcontrolled at baseline with mean HbA1c of 7.2% (55 mmol/mol), which is better than what has been reported for other studies assessing the impact of isCGM, [14][15][16]28,46,47 for general populations followed through diabetes registries, [48][49][50][51] and even for the whole Belgian pediatric population. 52 We are the first to follow a population up to 24 months after isCGM initiation.…”
Section: Self-reported Adverse Events and Complaints With Iscgmmentioning
confidence: 73%
“…Studies with poorly controlled subjects observed a modest decrease in HbA1c after 2 to 3 months. 14,28,46,47 Only one of these studies followed the study population for a longer period of time, here HbA1c was not different after 12 months of isCGM use than at baseline. 14 31,32,54 In addition, it has been reported that pressureinduced sensor attenuation can cause false low measurements, 55 especially seen at night, and thus hyperglycemia due to unnecessary carbohydrate intake.…”
Section: Self-reported Adverse Events and Complaints With Iscgmmentioning
confidence: 99%